Proteolytic regulation of metabolic enzymes by E3 ubiquitin ligase complexes: lessons from yeast. (2nd November 2015) - Nakatsukasa, Kunio; Okumura, Fumihiko; Kamura, Takumi
Abstract: Eukaryotic organisms use diverse mechanisms to control metabolic rates in response to changes in the internal and/or external environment. Fine metabolic control is a highly responsive, energy-saving process that is mediated by allosteric inhibition/activation and/or reversible modification of preexisting metabolic enzymes. In contrast, coarse metabolic control is a relatively long-term and expensive process that involves modulating the level of metabolic enzymes. Coarse metabolic control can be achieved through the degradation of metabolic enzymes by the ubiquitin-proteasome system (UPS), in which substrates are specifically ubiquitinated by an E3 ubiquitin ligase and targeted for proteasomal degradation. Here, we review select multi-protein E3 ligase complexes that directly regulate metabolic enzymes in Saccharomyces cerevisiae . The first part of the review focuses on the endoplasmic reticulum (ER) membrane-associated Hrd1 and Doa10 E3 ligase complexes. In addition to their primary roles in the ER-associated degradation pathway that eliminates misfolded proteins, recent quantitative proteomic analyses identified native substrates of Hrd1 and Doa10 in the sterol synthesis pathway. The second part focuses on the SCF (Skp1-Cul1-F-box protein) complex, an abundant prototypical multi-protein E3 ligase complex. While the best-known roles of the SCF complex are in the regulation of the cell cycle and transcription, accumulating evidence indicates that the SCF complex also modulates carbon metabolism pathways. The increasing number of metabolic enzymes whose stability is directly regulated by the UPS underscores the importance of the proteolytic regulation of metabolic processes for the acclimation of cells to environmental changes.